Effectiveness of digital health applications on the quality of life in patients with overweight or obesity: a systematic review - Melanie Mäder; Tonio Schönfelder; Ria Heinrich; Carsta Militzer-Horstmann; Patrick Timpel (Archives of Public Health)
Abstract Background Globally, more than half of the adult population is overweight, including those who are obese, which increases the risk of premature death and reduces quality of life (QoL). Technologies such as digital health applications (DiHA) can potentially improve clinical outcomes (e.g., health status, illness duration, QoL) or patient-related factors (e.g., therapy monitoring, adherence, health literacy). To date, there is no systematic review addressing the effectiveness of DiHA on the QoL in patients with overweight or obesity. Objective The objective was to investigate the impact of DiHA on QoL in overweight or obese patients. Methods A systematic literature search was conducted in MEDLINE via PubMed, Cochrane Library, and Embase via Ovid in 2023, supplemented by additional manual searches. The eligibility criteria included patients with overweight and/or obesity who used a digital intervention independently and without interaction with a healthcare professional. The outcome of interest was QoL. As potentially eligible trials had to demonstrate effectiveness, only randomized controlled trials (RCT) were included as the minimum evidence standard. The study screening (title-abstract, full-text) was conducted independently by two researchers using pre-specified eligibility criteria. CONSORT-EHEALTH checklist was used for data extraction of qualitative and quantitative data (study characteristics and study results) and the Cochrane Risk of Bias Tool (version 2) for quality assessment independently by two researchers. Results Seven RCT conducted in Europe and the United States were included in this systematic review with a total sample size of N = 946. Observation periods were heterogeneous and ranged from 3 to 24 months. The evaluated interventions consisted of websites or apps, all of which included nutrition and physical activity features, and functioned independently with minimal or no involvement of a healthcare professional. All studies showed a high risk of bias, no statistically significant improvement and no effects regarding QoL using different validated questionnaires. Conclusions This systematic review provides a comprehensive analysis of DiHA effectiveness on QoL in patients with overweight or obesity. Overall, there is heterogeneity regarding the operationalization of QoL and the examined interventions have no statistically significant impact on QoL. Comparable systematic reviews show that digital interventions have the potential to improve the QoL of these patients, but further RCT and high-quality studies are needed to assess the impact of DiHA on QoL. Trial registration PROSPERO CRD42023408994.